Test of variables of attention (TOVA) as a predictor of early attention complaints, an antecedent to dementia - Eric R Braverman (Dove Medical Press, 2010)
Eric R Braverman1,5, Amanda Lih-Chuan Chen2, Thomas JH Chen3, John D Schoolfield4, Alison Notaro5, Dasha Braverman5, Mallory Kerner5, Seth H Blum6 , Vanessa Arcuri5, Michael Varshavskiy5, Uma Damle5 , B William Downs7, Roger L Waite7, Marlene Oscar-Berman8, John Giordano9 , Kenneth Blum5,6,7,101Division of Neurological Surgery, Weill Cornell College of Medicine, New York, NY, USA; 2Department of Engineering and Management of Advanced Technology, 3Department of Occupational Safety and Health, Chang Jung Christian University, Tainan, Taiwan Republic of China; 4Department of Periodontics, University of Texas, Health Science Center, San Antonio, TX, USA; 5PATH Research Foundation, New York, NY, USA; 6Department of Nutritional Genomics, Synaptamine, Inc., San Antonio, TX, USA; 7Department of Personalized Medicine, LifeGen, Inc., La Jolla, CA, USA; 8Boston University School of Medicine, Boston VA, Boston, MA, USA; 9Department of Holistic Medicine, G & G Holistic Addiction Treatment Center, North Miami Beach, FL, USA; 10Department of Physiology and Pharmacology, University of Wake Forest School of Medicine, Medical Center Boulevard, Winston-Salem, NC, USAAbstract: The goal of this study was to determine if impairments detected by the test of variables of attention (TOVA) may be used to predict early attention complaints and memory impairments accurately in a clinical setting. We performed a statistical analysis of outcomes in a patient population screened for attention deficit hyperactivity disorder or attention complaints, processing errors as measured by TOVA and the Wechsler Memory Scale (WMS-III) results. Attention deficit disorder (ADD) checklists, constructed using the Diagnostic and Statistical Manual of Mental Disorders 4th Edition criteria, which were completed by patients at PATH Medical, revealed that 72.8% of the patients had more than one attention complaint out of a total of 16 complaints, and 41.5% had more than five complaints. For the 128 males with a significant number of ADD complaints, individuals whose scores were significantly deviant or borderline (SDB) on TOVA, had a significantly greater number of attention complaints compared with normals for omissions (P < 0.02), response time (P < 0.015), and variability (P < 0.005), but not commissions (P > 0.50). For males, the mean scores for auditory, visual, immediate, and working memory scores as measured by the WMS-III were significantly greater for normals versus SDBs on the TOVA subtest, ie, omission (P < 0.01) and response time (P < 0.05), but not variability or commissions. The means for auditory, visual, and immediate memory scores were significantly greater for normals versus SDBs for variability (P < 0.045) only. In females, the mean scores for visual and working memory scores were significantly greater for normals versus SDBs for omissions (P < 0.025). The number of SDB TOVA quarters was a significant predictor for “impaired” or “normal” group membership for visual memory (P < 0.015), but not for the other three WMS-III components. For males, the partial correlation between the number of attention complaints and the number of SDB TOVA quarters was also significant (r = 0.251, P < 0.005). For the 152 females with a significant number of attention complaints, no significant differences between SDBs and normals were observed (P > 0.15). This is the first report, to our knowledge, which provides evidence that TOVA is an accurate predictor of early attention complaints and memory impairments in a clinical setting. This finding is more robust for males than for females between the ages of 40 and 90 years.Keywords: attention complaints, dementia, TOVA, Wechsler Memory Scale